2023
DOI: 10.1098/rsos.230644
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and future challenges in gene therapy for hearing loss

Abstract: Hearing loss is the most common sensory deficit experienced by humans and represents one of the largest chronic health conditions worldwide. It is expected that around 10% of the world's population will be affected by disabling hearing impairment by 2050. Hereditary hearing loss accounts for most of the known forms of congenital deafness, and over 25% of adult-onset or progressive hearing loss. Despite the identification of well over 130 genes associated with deafness, there is currently no curative treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Insights from ongoing clinical trials centered on eye treatments have indicated that viral gene therapy might induce an adaptive immune response. This observation raises optimism for similar prospects in the inner ear domain [9,120,121].…”
Section: Implications Of the Immune Responsementioning
confidence: 88%
See 1 more Smart Citation
“…Insights from ongoing clinical trials centered on eye treatments have indicated that viral gene therapy might induce an adaptive immune response. This observation raises optimism for similar prospects in the inner ear domain [9,120,121].…”
Section: Implications Of the Immune Responsementioning
confidence: 88%
“…While the potential application of these therapeutic strategies to humans is now within closer reach than ever, substantial challenges remain on the horizon. These include optimizing the treatment's transduction efficiency and specificity through more targeted capsids and promoters, identifying superior delivery methods, and a deeper comprehension of potential treatment side effects [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular therapies such as gene replacement, gene suppression, antisense oligonucleotides, RNA interference, and CRISPR-based gene editing [59][60][61][62], as well as precise delivery methods, techniques, and viral vectors employed for inner ear gene therapy are actively under investigation [63][64][65][66][67]. Gene therapy for HL is actively growing, and exciting new genetherapy-based strategies to restore and prevent SNHL are arising [59] with proof-of-principle studies demonstrating the therapeutic potential of molecular agents delivered to the inner ear to treat or ameliorate different types of SNHL [68,69]. These advancements are rapidly paving the way for basic science research discoveries to transition to clinical trials, with genetic testing being foundational for the development of novel personalized therapeutic options.…”
Section: Individualized Prevention and Treatment For Snhlmentioning
confidence: 99%
“…Unfortunately, several failures of drug candidates in clinical phase have dampened the interest of pharmaceutical companies in the field. The main encouraging pathway is currently gene therapy, among those targeting genetic deafness caused by otoferlin mutation, with promising results in clinical trials ( Amariutei et al, 2023 ; Ha and Avraham, 2023 ; Lv et al, 2024 ). Though otoferlin-related hearing loss is very rare, accounting for only 1–8% of cases of hereditary deafness ( Ford et al, 2023 ), the results offer hope for treating other genetic forms of deafness.…”
Section: Introductionmentioning
confidence: 99%